Re-Constructing the Tutors-Tutees Relationships for Better Academic Performance in Universities Amidst Covid-19 New Normal - Omodan, Bunmi Isaiah; Ige, Olugbenga A. (Richtmann Publishing, 2021)
In the past, the success of Supplemental Instruction (Tutorial Sessions) depends on the tutors and tutees' physical and social relationships. However, the assumption exists that when there are no physical connections between the duos may affect their social interrelationships, impeding the success and intention of SI in the University classrooms. This study, therefore, investigates the current relationships amidst new normal towards SI and students performance. The study is underpinned by attachment theory to unravel the extent, importance and shortcomings of the assumed change in the relationship between the understudied. The study is guided by the Transformative Paradigm (TP) and Participatory Research (PR) to identify the possible dichotomies in their relationships. Purposive selection method was used to select five tutors and five tutees in a selected university in South Africa. Online (WhatsApp, email, and telephonic) interview was used to collect data from the participants. The data were subjected to thematic analysis. The result showed that that; struggles with the use and lack of Internet-of-Things and unstructured work-hours were the significant challenges that affected online tutorial sessions. On the other hand, the study also found out that students need ICT training and devices, including motivation for performance. Therefore, we recommend that training of ICT and provision of devices alongside strong motivation should be ensured. Received: 1 February 2021 / Accepted: 3 March 2021 / Published: 7 March 2021